Meek or oppressed? Reading Matthew 5:5 in context - W. Domeris (Acta Theologica)
According to the Gospel of Matthew 5:5, Jesus pronounces a blessing on “the meek” (Greek ?? ??????), promising that they will receive the inheritance of the earth (or land). The words of Jesus are a quotation from the LXX of Psalm 37:11 and each of the Hebrew terms (subject, object and verb) need careful consideration. Following, the Hebrew original we might translate the verse in Psalm 37:11 as “The oppressed/ humiliated will take possession of the land”. The force of the original saying finds its meaning in the wider context of the Psalm, where wealthy landowners threaten theinterests of ordinary peasants and they cry out to God for justice. The variance between the Hebrew (MT) and the Greek (LXX) raises anew the interpretation of these words of Jesus. Who did Matthew’s Jesus have in mind - the meek of emerging Christianity or the poor and humiliated peasants, who made up the majority of his Palestinian audience? In this article, I consider the implications of Jesus addressing a peasant audience in a conversation about taking possession of farming land and then extend this discussion into the emerging peasant realities of the post-revolutionary context in Galilee and Judaea. In the light of the present archaeological data, and the rabbinic sources, peasant life continued more or less unchanged with little indication of large-scale estates.